Activity Test of Dexamethasone Therapy to Humoral Immunity in Balb/c Mice with Biliary Atresia - Churi Wardah; Muhaimin Rifa'i (Biotropika: Journal of Tropical Biology, 2014)
The prevalence of biliary atresia is 1:5.000-8.000 of live births. Kasai portoenterostomy is a reliable treatment, but liver damage continues. Dexamethasone (corticosteroid) evolved into a commonly used therapy and is believed to improve clinical outcomes in biliary atresia. The objective of this study was to determine the effect of dexamethasone on the absolute number of IgA, IgD, IgE, IgG, and IgM in mice Balb/c model of biliary atresia. Murine model of biliary atresia obtained by injection of 20 μL of PBS containing 106 pfu Rhesus rotavirus (RRV) at <24 hours of mice age. Injection of dexamethasone with dose of 0.5 mg/kg body weight was done on day 7 to day 14, and day 14 to day 21 after virus injection. Spleen taken for analysis of flow cytometry. Data were tested with Kruskal-Wallis test, then follow up the Man-Whitney test to assess   the difference with SPSS 16.0 for Windows. Here, we show significant difference of immunoglobulin molecule in both termination (p<0.05). Subcutaneously injection of RRV (Rhesus Rotavirus) in Balb/c mice in the of aged <24 hours is capable to stimulate the production of immunoglobulin, especially at the termination of the third week. This can be evidenced by an increase in IgD, IgA, IgD, and IgG. Dexamethasone is glucocorticoid that plays role as immunosuppressant with ability in decreasing IgD, IgM, IgD, and IgG levels in both termination. Furthermore we showed that dexamethasone was capable of stimulating the production of IgA in third week. Keywords : Balb/c baby mice, Biliary atresia, Corticosteroid, Dexamethasone, Rhesus Rotavirus